PERANCANGAN GAME 3D TOWER DEFENSE BERBASIS UNITY ENGINE - Michael Yosua; Kussigit Santosa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Games are one of the many entertainment media that are growing rapidly along with the development of information and communication technology, and the genres in games are also growing rapidly and are increasingly varied nowadays. One of the genres in the game is strategy. Tower defense game is a subgenre of strategy game, the main goal of Tower defense game is to protect an area so that it is not passed by enemies who walk on a predetermined path by building a tower placement strategy that will attack enemies so they don't get to that area. Usually the towers that are built have differences in their effectiveness when attacking or shooting enemies. Players will get points if they succeed in defeating enemies which can be used to build towers that aim to provide additional damage or a different shooting range.